Literature Review: Analisis Peran Humas Menerapkan Komunikasi Dua Arah Dalam Membangun Kemitraan Sekolah dan Masyarakat - Farida Ariani; Reflianto Reflianto (Institut Agama Islam Sumatera Barat, 2024)
This research aims to examine the development of public relations theory and its implementation in the educational context, particularly regarding the two-way communication model developed by Grunig. The research method employs a literature study approach by analyzing various international research findings on public relations practices in schools. The results show that although the symmetrical two-way communication model is considered ideal, there are still significant gaps in its implementation within the school environment. Schools tend to implement one-way communication focusing on promotion and persuasion, neglecting aspects of dialogue and partnership with the community. The main challenges include limited competencies of public relations staff, underutilization of digital technology, and the dominance of control paradigms in school management. The digital era opens new opportunities to build more effective interactive communication, but requires fundamental transformation in schools' public relations approach. This research recommends developing a more structured public relations management system, enhancing staff competencies through cross-disciplinary education, optimizing digital media usage, and strengthening leadership roles in building a culture of dialogue with the community. The theoretical and practical implications of these findings contribute to the development of more effective public relations models in contemporary educational contexts